Human Relations Training for Families: A Counselling Strategy - Ford, Blake G.; West, Lloyd W. (Canadian Journal of Counselling and Psychotherapy, 2012)
To evaluate the efficacy of a human relations training program for parents of personality disorder pre-adolescent boys, sixty families were randomly assigned to four experimental groups: 1) Control, 2) Mother, 3) Mother-Father, 4) Mother-Father-Child. Pre- and posttest measure of Parents' and Subjects' behaviour were obtained by audio and video tape recordings of family interaction in a standardized laboratory setting. Significant differences between groups at posttesting were found on four dependent variables: Empathy, Warmth, and Genuineness of Parents, and Positive Assertive Behaviour of Subjects.